Increased coronary heart disease in Japanese-American men with mutation in the cholesteryl ester transfer protein gene despite increased HDL levels. - Zhong, S (1996)
Plasma high density lipoprotein (HDL) levels are strongly genetically determined and show a general inverse relationship with coronary heart disease (CHD). The cholesteryl ester transfer protein (CETP) mediates the transfer of cholesteryl esters from HDL to other lipoproteins and is a key participant in the reverse transport of cholesterol from the periphery to the liver. A high prevalence of two different CETP gene mutations (D442G, 5.1%; intron 14G:A, 0.5%), was found in 3,469 men of Japanese ancestry in the Honolulu Heart Program and mutations were associated with decreased CETP (-35%) and increased HDL chol levels (+10% for D442G). However, the overall prevalence of definite CHD was 21% in men with mutations and 16% in men without mutations. The relative risk (RR) of CHD was 1.43 in men with mutations (P < .05); after adjustment for CHD risk factors, the RR was 1.55 (P = .02); after additional adjustment for HDL levels, the RR was 1.68 (P = .008). Similar RR values were obtained for the D442G mutation alone. Increased CHD in men with mutations was primarily observed for HDL chol 41-60 mg/dl; for HDL chol > 60 mg/dl men with and without mutations had low CHD prevalence. Thus, genetic CETP deficiency appears to be an independent risk factor for CHD, primarily due to increased CHD prevalence in men with the D442G mutation and HDL cholesterol between 41 and 60 mg/dl. The findings suggest that both HDL concentration and the dynamics of cholesterol transport through HDL (i.e., reverse cholesterol transport) determine the anti-atherogenicity of the HDL fraction.